Fertilizer Management for Maximizing Soybean (Glycine max L.) Production in Char Lands of Bangladesh (The Agriculturists, 2015)
An experiment was conducted at Char Martin under Multi Location Testing site in Laxmipur district during Rabi season of 2011-12 & 2012-13 with different fertilizer doses to find out the economic fertilizer dose for soybean variety BARI Soybean 6 under farmers field condition. Four fertilizer combinations viz; T1 : 17-27-55-2.7-2.0-0 kg ha-1 of N-P-K-S-Zn-B (Soil Test Based fertilizer), T2 : 25- 25-50-10-0-0 kg ha-1 of N-P-K-S-Zn-B (Fertilizer Recommendation Guide, 2005 based fertilizer), T3 : 28-13-0-0-0-0 kg ha-1 of N-P-K-S-Zn-B (Farmers practice) and T4: Native fertility (control) were selected. All the yield and yield contributing characters of BARI Soybean 6 varied significantly with the different fertilizer treatments. The highest seed yield (2.99 t ha-1) was recorded from plants treated with T1 which was statistically similar to T2. The lowest seed yield (1.74 t ha-1) was obtained from T4. The highest gross return (Tk.104650 ha-1), net return (Tk. 56375 ha-1) and benefit cost ratio (2.16) were obtained from T1 and the lowest gross return (Tk. 60900 ha-1), net return (Tk.19900 ha-1) and BCR (1.48) was obtained from T4 .The Agriculturists 2014; 12(2) 98-102